Key distribution scheme of wireless sensor networks based on logic grid - HUANG Hai-ping1; 2; WANG Ru-chuan1; 2 (Tongxin xuebao)
Owed to the obvious characters of energy-constraint and dynamic topology, issues including confidentiality, integrality, authentication and no sufficient memory for abundance of key information, needed to be effectively solved in key management technique, especially in wireless sensor networks （abbreviation for WSN） applications. Aimed at some limitations like these on current research work, a key distribution scheme based on logic grid of WSN was proposed, which used the layer-cluster topologic structure. The complete process was described, involving resolution of coefficient matrix, keys’ initialization and specific realization. Compared with some other schemes, such as SPIN protocol and logic key tree methods, simulation results show its advantages on security, memory performance and energy- consumption, etc..